(3GdJdbjf aj Gdabg GdeGdcis - (3CHh eMeO YHO GdhgGH Hf Ydj Hf fUQ GdHZOGOj GdbQGaj GdeGdcjs ((3GHQGgje Hf jMji Hf eMeO s)
(3ChdgG (B:s
(3bGd GdbGVi CHh eMeO YHO GdhgGH fMeO Gddg hfTcQg hfSJYjfg cJGH GdWgGQI s
(3BNQgG (B:s
(3hef QCi ai efGeg TjFkG jcQgg Jad Yf jSGQg KdGKkG hJYhP HGddg efg hGdMeO ddg , hbO CJjfG ai gPG GdeNJUQ eG fSCd Gddg GdfaY dfG Hg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(672(3L(B) s
Keywords: (3Gdabg GdeGdcjs